2016
DOI: 10.1093/rheumatology/kew313
|View full text |Cite
|
Sign up to set email alerts
|

Calcinosis is associated with digital ischaemia in systemic sclerosis—a longitudinal study

Abstract: Ischaemia may play a role in the development of calcinosis in SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
3
44
1
1
Order By: Relevance
“…Only prospective longitudinal studies with long-term followup will allow us to draw conclusions regarding any common causal factors of micro-and macrovascular involvement. Two recent studies have highlighted the associations of calcinosis with digital ischemia and late NFC pattern in SSc (2,3). Morardet et al (2) have also reported an association between acroosteolysis and late NFC pattern.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Only prospective longitudinal studies with long-term followup will allow us to draw conclusions regarding any common causal factors of micro-and macrovascular involvement. Two recent studies have highlighted the associations of calcinosis with digital ischemia and late NFC pattern in SSc (2,3). Morardet et al (2) have also reported an association between acroosteolysis and late NFC pattern.…”
Section: Discussionmentioning
confidence: 98%
“…There is a lack of therapeutic measures to tackle these digital manifestations of the disease, and a better characterization of the mechanisms underlying acroosteolysis and calcinosis is therefore needed. Recent cross-sectional studies have reported an association of these digital manifestations with Cutolo's late capillaroscopic pattern, defined by severe capillary loss and proliferative neovascularization, supporting a vascular etiology of both acroosteolysis and calcinosis (2,3).…”
Section: Introductionmentioning
confidence: 92%
“…It is posited that tissue ischemia by vasculopathy may contribute to the development of cutaneous calcinosis . However, the pathogenesis of spinal calcinosis in SSc is not well‐known.…”
Section: Discussionmentioning
confidence: 99%
“…It is posited that tissue ischemia by vasculopathy may contribute to the development of cutaneous calcinosis. [7][8][9] However, the pathogenesis of spinal calcinosis in SSc is not wellknown. Ogawa et al 15 reported that Raynaud's phenomenon and digital ulcers were significantly prevalent in SSc patients with spinal calcinosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation